Risk, Return, and the Morphology of Commercial Banking - Emery, John T. (Journal of Financial and Quantitative Analysis, 1971)
To assure that the commercial banking industry's performance serves the “convenience and needs” of the public, bank supervisory authorities have been vested with broad powers to alter the competitive environment in bank markets. While several criteria have been used to evaluate the effects of entry, merger, branching, and other changes in the allocation of bank resources, the results have been largely inconclusive. Since the regulatory authorities have pursued somewhat conflicting objectives in seeking a “failure-proof” system that is also “efficient, ” there may be no single criterion for evaluation of bank behavior that is wholly consistent with the behavior predicted by the neoclassical theory of the firm.